Analysis of crystalline structure and morphology of isotactic polypropylene under the coexistence of organic montmorillonite particles and shear flow. (15th January 2016) - Lei, Fan; Yu, Huaning; Yang, Shuo; Sun, Huimin; Li, Jiang; Guo, Shaoyun; Wu, Hong; Shen, Jiabin; Chen, Rong; Xiong, Ying
Abstract: In this work, the different effects of organic montmorillonite (OMMT) particles and shear flow on the crystallization behavior of isotactic polypropylene (iPP) were discussed. While neat iPP and OMMT filled iPP were treated using the multistage stretching extrusion technology, changing the number of laminating-multiplying elements (LMEs) can obtain samples with different dispersion degree of OMMT particles and different orientation degree of molecular chains. With the increase of LME number, the content of β-crystal in neat iPP increased. But for OMMT/iPP composites, decreasing LME number caused the increase of content of β-crystal. The experimental results showed that the shear flow and large OMMT aggregations were essential factors for the formation of β-crystal in composites, and the crystalline morphology strongly depended on the size of OMMT particles. The scanning electron microscope (SEM) images of sample with 3 wt% of OMMT particles and without LME illustrated that β-transcrystallinity, fan-shaped β-crystal and α-spherulite were induced by different size of OMMT particles, respectively. A schematic was proposed to describe the formation mechanism of α-crystal and β-crystal under the coexistence of OMMT particles and shear flow. Graphical abstract: Highlights: The content of β-crystal in neat iPP was enhanced with increasing number of (LME). The content of β-crystal in OMMT/iPP composites was decreased with increasing number of LME. The dispersion of OMMT in iPP matrix was improved by increasing shear force. The dimensions of OMMT particles influenced the morphology of iPP crystal. A schematic was proposed to describe the formation mechanism of α-crystal and β-crystal.